Human Lobomycosis Caused by Paracoccidioides (Lacazia) loboi, Panama, 2022 - Jose A. Suárez; Betty Cerrud; Monica Pachar; Luz H. Patiño; Jason Reidy; Amina Chace; Roderick Chen-Camaño; Diógenes Alvarado-Barría; Mohammad Z. Nakadar; Juan D. Ramirez; Alberto Paniz-Mondolfi (Emerging Infectious Diseases, 2023)
We report a patient from Panama who had lobomycosis caused by Paracoccidioides (Lacazia) loboi. We used combined clinical-epidemiologic and phylogenetic data, including a new gene sequence dataset on this fungus in Panama, for analysis. Findings contribute useful insights to limited knowledge of this fungal infection in the Mesoamerican Biologic Corridor.